Generalized Iteration Method via Green's Function for the Solution of the Fourth-order Boundary Value Problems (European Journal of Pure and Applied Mathematics, 2021)
The aim of this paper is to extend and generalize Picard-Green’s fixed point iteration method for the solution of fourth-order Boundary Value Problems. Several numerical applications to linear and nonlinear fourth-order Boundary Value Problems are discussed to illustrate the main results.
Keywords: Boundary value problems; iteration method; Green's function; integral operator; rate of convergence